2019
DOI: 10.1130/g46491.1
|View full text |Cite
|
Sign up to set email alerts
|

Cold and dry outbreaks in the eastern Mediterranean 3200 years ago

Abstract: Can climate affect societies? This question, of both past and present importance, is encapsulated by the major socioeconomic crisis that affected the Mediterranean 3200 yr ago. The demise of the core civilizations of the Aegean and eastern Mediterranean during the Late Bronze Age and the early Iron Age (Dark Ages) is still controversial because it raises the question of climate-change impacts on ancient societies. Although evidence for this climate shift has gradually gained currency, recent attempts to quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…The climate reconstruction from Tell Tweini, coastal Syria (mainland), closely mirrors the data from Hala Sultan Tekke for the period 3500–2500 BP (Kaniewski et al, 2019a). In situ bioarcheological studies from Pyla‐ Kokkinokremnos (~15 km from Hala Sultan Tekke, Cyprus) and Tell Tweini (~220 km to the northwest) support this correlation as similar dry environments were recorded during the LBA collapse (Kaniewski et al, 2019b). On Cyprus, populations were able to overcome summer drought by pumping freshwater from the aquifers of the Tremithos River (Ploethner et al, 1986; Ghilardi et al, 2011) as the lake only fills during winter time, fed by precipitation.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…The climate reconstruction from Tell Tweini, coastal Syria (mainland), closely mirrors the data from Hala Sultan Tekke for the period 3500–2500 BP (Kaniewski et al, 2019a). In situ bioarcheological studies from Pyla‐ Kokkinokremnos (~15 km from Hala Sultan Tekke, Cyprus) and Tell Tweini (~220 km to the northwest) support this correlation as similar dry environments were recorded during the LBA collapse (Kaniewski et al, 2019b). On Cyprus, populations were able to overcome summer drought by pumping freshwater from the aquifers of the Tremithos River (Ploethner et al, 1986; Ghilardi et al, 2011) as the lake only fills during winter time, fed by precipitation.…”
Section: Resultsmentioning
confidence: 76%
“…Around 3200 BP (~ Cp 3 ), LBA societies declined and finally disintegrated, affected by both internal conflicts and migrations (the Sea Peoples phenomenon), leading to deep‐seated sociocultural changes that lasted roughly 300 years. While this crisis was essentially rooted in political struggles and socioeconomic tensions, recent studies have suggested that a centuries‐long drought and climate cooling underpinned the decline (Kaniewski et al, 2008, 2019ab).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The society in the past was extremely fragile in front of major climate change episodes and their broader consequences (Kaniewski et al., 2019; Zhang et al., 2008). Fundamentally, the rice agriculture was vulnerable to natural disasters, especially to drought or flood which can result in lower yields or less cultivated acreages.…”
Section: Society Development and The Motivation Of Cliff Paintingmentioning
confidence: 99%
“…A plethora of historical, archaeological and geological evidence evokes synchroneity between major palaeoclimatic changes and socio-economic/political crises in West Asia ( Kaniewski et al. 2012 , 2018 , 2019 ; Sharifi et al., 2015 ). The timing of these events cannot be dismissed as simply pure coincidence and, regarding their geographical extent, the factors driving these changes were undoubtedly large scale ( Kennett and Kennett 2007 ; Caspers 1971 ; Hole 1994 ; Gurjazkaite et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%